(untitled) (Colombia Medica, 2008)
Vertiginous world wide changes also trigger transformation along the organizations, including health enterprises. The future enterprises must be multilevel functional and have defined their strategic goals including definition of processes facilitating their operation. Actually at all level health teaching enterprises should have a thought strategic direction and defined operative rules in order to have a functional structure that facilitates taking decisions and consequently have defined processes that allow them to respond appropriately to the influence of the environment and other social actors. The success key for modern organizations is to have an appropriate philosophy and managerial culture, to possess deep knowledge of the area of business, to have political managed and constructive rules for both: the internal and external clients in order to offer quality services, to rule appropriate communication models and to make a permanent evaluation of the environment. All that must allow them to respond appropriately to threats and opportunities.